Characterization of Several 2-Ethylhexyl Nitrates with Vegetable Oil (Castor or Sunflower Oil) Blends in Triple Blends with Diesel, Working as Advanced Biofuels in C.I. Diesel Engines - Rafael Estevez; Francisco J. López-Tenllado; Vicente Montes; Antonio A. Romero; Felipa M. Bautista; Diego Luna (Applied Sciences)
This study evaluates the performance of biofuels created from triple blends of fossil diesel, sunflower or castor oil (SVOs), and 2-Ethylhexyl Nitrate (EHN), a low-viscosity, high-cetane (LVHC) solvent. EHN reduces the viscosity of SVOs to enable their use in conventional diesel engines without compromising fuel properties. The results show that the power output from these blends is similar to or greater than that of fossil diesel, with comparable fuel consumption. Furthermore, the blends significantly reduce emissions of carbon monoxide (CO) and soot, though NOx emissions are slightly higher due to the nitrogen content in EHN. However, NOx levels remain within permissible limits. The substitution of fossil diesel could be further enhanced if EHN were produced using green hydrogen and lignocellulosic biomass, making it a renewable and sustainable biofuel component. These findings support the potential of EHN/SVO biofuel blends to replace a significant portion of fossil diesel in conventional diesel engines while maintaining performance and reducing harmful emissions, except for a slight increase in NOx.